MENANAMKAN RASA KESADARAN HUKUM DALAM BERLALU LINTAS PADA ANAK USIA DINI - Tika, Rahma; Suryanti, Rini; Winarti, Winarti; Dewi, Iratna; Dafriyon, Dafriyon (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This research is based on the problems in traffic at the present time. In connection with this, solutions are needed to deal with traffic problems in order to create order and safety in traffic. This study aims to see how to instill legal awareness in traffic in early childhood. This study uses a type of research method or library research approach, namely library studies or literature can be interpreted as a series of activities related to the method of collecting library data, reading and recording and processing research materials. The results of the study indicate that instilling legal awareness in traffic in early childhood can be developed by introducing traffic sign symbols, how to walk on the highway correctly, understanding zebra crossings and how to cross properly and so on. Through integrating the early childhood education curriculum, through themes that are adjusted to learning about traffic. Then counseling or socialization and the need for cooperation between educators, parents, the community, government agencies, institutions and other stakeholders. Children who have an understanding of traffic rules and ethics will be more likely to develop safe and responsible habits on the road.So that it has an impact on the safety of the child it self, creating a more disciplined society and can provide a strong foundation for children in facing life in the future.Keywords: Planting, Legal Awareness, Traffic, Early Childhood